Pharmacogenic and neurologic components of residual condition in schizophrenia - V. V. Chuhunov; V. I. Darii; D. M. Safonov (Zaporožskij Medicinskij Žurnal)
Aim. To systematize neuroleptic-induced and neurologic components of residual condition in schizophrenia.